A case of acute monocytic leukemia (AMoL or AML‐M5) in an adult FeLV/FIV‐positive cat. (25th March 2021) - da Silva Serpa, Priscila Beatriz; Messick, Joanne B.
Abstract: A 7‐year‐old castrated male domestic shorthair cat was presented for evaluation of decreased appetite and respiratory signs. A CBC run on presentation revealed severe nonregenerative anemia, thrombocytopenia, and leukocytosis characterized by a prominent population of blasts, having morphologic features suggestive of a monocytic lineage. The cat tested positive for FIV, FeLV, Mycoplasma haemominutum, and only mild abnormalities were identified on the chemistry panel. Bone marrow biopsies were obtained to investigate the bicytopenia and the possibility of a hematopoietic neoplasm. Although the bone marrow aspirate was nondiagnostic, the core biopsy was markedly hypercellular with a population of blasts, largely replacing the normal hematopoietic tissue. Immunohistochemical staining revealed that the blasts were CD3‐negative, Pax5‐negative, dimly CD18‐positive, and moderately positive for Iba1. These findings, in addition to the prominent monocytic differentiation seen in peripheral blood, supported a diagnosis of acute monocytic leukemia. Palliative antiviral and antibiotic treatment and blood transfusion were performed. The patient was discharged on his fourth day of hospitalization. However, 15 days following discharge, the cat was euthanized due to the worsening of his systemic signs. This report discusses the classifications of myeloid leukemias, implications of infectious diseases in the pathogenesis of neoplasia in cats, and the use of Iba1, a "pan‐monocytic/histiocytic" marker, in the diagnosis of acute leukemia.